Proteomic analysis reveals distinctive protein profiles involved in CD8+ T cell-mediated murine autoimmune cholangitis. Issue 8 (August 2018) - Zhang, Weici; Zhang, Ren; Zhang, Jun; Sun, Ying; Leung, Patrick; Yang, Guo-Xiang; Shuai, Zongwen; Ridgway, William; Gershwin, M
Abstract Autoimmune cholangitis arises from abnormal innate and adaptive immune responses in the liver, and T cells are critical drivers in this process. However, little is known about the regulation of their functional behavior during disease development. We previously reported that mice with T cell-restricted expression of a dominant negative form of transforming growth factor beta receptor type II (dnTGFβRII) spontaneously develop an autoimmune cholangitis that resembles human primary biliary cholangitis (PBC). Adoptive transfer of CD8+ but not CD4+ T cells into Rag1−/− mice reproduced the disease, demonstrating a critical role for CD8+ T cells in PBC pathogenesis. Herein, we used SOMAscan technology to perform proteomic analysis of serum samples from dnTGFβRII and B6 control mice at different ages. In addition, we analyzed CD8 protein profiles after adoptive transfer of splenic CD8+ cells into Rag1−/− recipients. The use of the unique SOMAscan aptamer technology revealed critical and distinct profiles of CD8 cells, which are key to biliary mediation. In total, 254 proteins were significantly increased while 216 proteins were significantly decreased in recipient hepatic CD8+ cells compared to donor splenic CD8+ cells. In contrast to donor splenic CD8+ cells, recipient hepatic CD8+ cells expressed distinct profiles for proteins involved in chemokine signaling, focal adhesion, T cell receptor and natural killer cell-mediated cytotoxicity pathways.